Evaluation of Epoxy-Based Fire Retardant Basalt Fibre Reinforced Intumescent Coating with Aluminum Trihydrate (ATH) for Fire Retardancy Protection of Structural Steel - Mohd Rodzhan, Nur Syahirah (IRC, 2016)
Intumescent coating is a paint-like material that swells or expands when it is exposed to fire in order to protect and maintain the strength integrity of the underlying substrate by providing an insulating char layer. The aims of this research are to investigate the effect of fillers on the char morphology structure and the thermal stability of the coating when reinforced with Aluminum Trihydrate (ATH) and basalt fibre for protection of the structural steel. Intumescent coating used consists of Ammonium Polyphosphate (APP), Expandable Graphite (EG), Melamine (MEL), Boric Acid (BA), ATH and basalt fibre as the fillers. Bisphenol A epoxy resin BE-188 (BPA) was used as a binder with Hardener H-2310 Polyamide Amine. A range of formulations with different compositions of ATH and basalt fibre were studied to evaluate their char expansion via Furnace Test. The char formation was characterized using Scanning Electron Microscopy and Energy Dispersive X-Ray Spectroscopy (SEM-EDS).